Influencia de la estacionalidad en la fertilidad de vacas Holstein altas productoras - Villa Mancera, Abel Edmundo (Universidad Autónoma Metropolitana, 2002)
The monthly fertility, was evaluated along the year, during the implicit period of 1991-2000. We used data records of reproduction of 24,380 artificial inseminations of high producer’s dairy cows. The study was made in "La Quinta Ranch" in Actopan, Hidalgo State, it is located an altitude of 1980 msnm, with a climate temperate semidry. We made an analysis of variance of mean square and a repeated measurement design to long the time to analyze the fertility and the climatic variables. The average of percent of fertility during the study was of 34.19, the rate of smaller success corresponds to the months of may to September (final of spring and during the summer), and highest success of October to april (autumn principle and winter, months with photoperiod of short days). Statistically we have that the winter-autumn season from the 1991-2000 period, and seasons along the study turned out to be significant (p < 0.01); while the months in seasons of year were not significant (p 0.05). The analysis of variance to the percentage of ferti1.Q didn't show differences to the light hours (p 0.05). Dry and rain seasons effects (november-march and april-october) in the fertility was significant (p 0.05). Correlation analysis showed to fertility variable, the minimum temperature was r = -0.82; in the same way, precipitation obtained in r = -0.86. Medium and minimum relative humidity, half wind speed have r = -0.69, -0.65, and -0.65 respectively, that viii shows a high correlation of these variables with the fertility. The results show that the maximum and minimum temperature, humidity relative minimum and maximum wind speed along of study period was statistically different (p c 0.05), in the same way, index temperature-humidity mean (p > 0.05). Is possible that climatic factors are modulating the fertility in the dairy cows.; Se evalud la fertilidad mensual de vacas Holstein altas productoras a lolargo del atlo, durante el período comprendido de 1991-2000, para ello se utilizaron los datos de los registros de 24,380 inseminaciones artificiales. El estudio se efectud en el rancho "La Quinta" en Actopan, Estado de Hidalgo, que estalocalizado a una altitud de 1980 msnm, con un clima semi seco templado. Se hizo un analisis de varianza de mínimos cuadrados, así como un diseflo de mediciones repetidas en el tiempo para evaluar la fertilidad y las variables climáticas. La media del porcentaje de fertilidad durante el estudio fue de 34.19, la tasa de menor éxito corresponden a los meses de mayo a septiembre (finales de primavera y durante el verano), y de mayor éxito de octubre a abril (principio de otoflo e invierno, meses con fotoperíodo de dCas cortos). Estadísticamente encontramos que las estaciones invierno-otofio del periodo 1991-2000, y las estaciones a lo largo del período de estudio resultaron ser significativas (PC 0.01); mientras que los meses que comprenden las estaciones del ano no fueron significativas. El anáisis de varianza para el porcentaje de fertilidad no mostró diferencias para las horas luz (p > 0.05). El efecto de las estaciónseca (noviembre-marzo) y de lluvias (abril-octubre) sobre la fertilidad result6 significativa (p < 0.05). El analisis de correlaci6n mostr6 que para la variable fertilidad, la temperatura mfnima, tuvo una r = -0.82 así como, r = -0.86 para la precipitación. La humedad relativa media y minima y velocidad del viento media tuvieron una r de -0.69, -0.65; y -0.65 respectivamente, lo que muestra una fuerte correlacidn de estas variables con la fertilidad. Los resultados muestran que la temperatura maxima y minima, la humedad relativa minima y velocidad del viento mdxima a lo largo del periodo de estudio resultaron ser diferentes estadisticamente (p < 0.05), asf como para el indice de temperatura-humedad media (p > 0.05). Por lo que es posible que los factores climáticos esté modulando la fertilidad en las vacas productoras de leche.